2021
DOI: 10.3390/plants11010051
|View full text |Cite
|
Sign up to set email alerts
|

Hairy CRISPR: Genome Editing in Plants Using Hairy Root Transformation

Abstract: CRISPR/Cas-mediated genome editing is a powerful tool of plant functional genomics. Hairy root transformation is a rapid and convenient approach for obtaining transgenic roots. When combined, these techniques represent a fast and effective means of studying gene function. In this review, we outline the current state of the art reached by the combination of these approaches over seven years. Additionally, we discuss the origins of different Agrobacterium rhizogenes strains that are widely used for hairy root tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 299 publications
(495 reference statements)
1
31
0
1
Order By: Relevance
“…The hairy root transformation system as a tool for CRISPR/Cas9-based genome editing has been established recently for various species (reviewed in Kiryushkin et al, 2022 ). Among Brassica crops, B. carinata hairy roots were successfully edited using a CRISPR/Cas9 system ( Kirchner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hairy root transformation system as a tool for CRISPR/Cas9-based genome editing has been established recently for various species (reviewed in Kiryushkin et al, 2022 ). Among Brassica crops, B. carinata hairy roots were successfully edited using a CRISPR/Cas9 system ( Kirchner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hairy root transformation has been recently discovered as an efficient tool for studying gene function using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPRs)/CRISPR-associated protein 9 (Cas9)-mediated gene editing in a wide range of plant taxa (reviewed in Kiryushkin et al, 2022 ). This bacterial system has been exploited to develop a powerful RNA-guided genome editing tool in various species.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it was suggested that RNA interference studies be replaced with this method. According to the literature, Cas9 protein is the most preferred and used for the development of genome-edited plants ( Kiryushkin et al, 2022 ). The expression of Cas9 under the cauliflower mosaic virus (CaMV) 35S promoter (p35S) was observed in a total of 78 plant-related genome-editing studies ( Amack and Antunes, 2020 ).…”
Section: Gene-editing Technologiesmentioning
confidence: 99%
“…It is mainly chosen when there are no protocols existing for stable transformation and regeneration, or the desired traits were only seen in roots ( Christey, 2001 ). Recently, a study described the possibility of editing the genomes of transgenic hairy roots using CRISPR/Cas9 ( Kiryushkin et al, 2022 ). This study concluded that by combining these techniques, it is possible to study gene function quickly and efficiently.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Hairy root transformation has been recently discovered as an efficient tool for studying gene function using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein 9 (Cas9)-mediated gene editing in a wide range of plant taxa (reviewed in Kiryushkin et al, 2021). This bacterial system has been exploited to develop a powerful RNA-guided genome editing tool in various species.…”
Section: Introductionmentioning
confidence: 99%